XCLK Frequency Optimization on ESP32-CAM and Telegram-Based Smart Doorbell Systems - M Raya Khashi Hega; Zulhipni Reno Saputra; Syarifah Aini (JURNAL TEKNOLOGI DAN OPEN SOURCE, 2026)
This research is motivated by the limitations of the conventional doorbell system that only uses sound indicators without providing visual information and remote notifications. The research aims to design and implement an Internet of Things (IoT)-based smart doorbell system using ESP32-CAM and Telegram and analyze the influence of XCLK frequency optimization on system stability and response. The method used is a prototype through the stages of design, implementation, testing, and evaluation of the system. The system was developed using the ESP32-CAM as the main controller and camera module, push button as a trigger, buzzer as a voice indicator, and Telegram Bot as a medium for sending real-time visual notifications. Tests were conducted on XCLK frequency variations of 1 MHz, 5 MHz, 20 MHz, 50 MHz, and 100 MHz to evaluate system performance. The results showed that the 20 MHz XCLK frequency produced the most optimal performance with stable image capture, faster system response, and consistent notification delivery. Low frequencies cause response delays, while high frequencies trigger instability and system restarts. Thus, XCLK frequency optimization is based on [pay attention again to foreign terms in italics. In the same journal, if foreign terms still have to be italicized.significantly affect the reliability and performance of the ESP32-CAM-based smart doorbell system.